Cavitation noise from elastic response of metals in ultrasonic cavitation erosion. (July 2016) - Ge, Han; Li, Jiang; Chen, Haosheng
Noise from the cavitation around propellers is the main noise source of marine vehicles. In our experiment, we found that the material of the propeller also affected the cavitation noise, especially on their frequencies. Three most commonly used metal propeller materials, including brass (B), aluminum bronze (AlB), and stainless steel (SS), were placed in an ultrasonic cavitation system. They presented different spectral peaks in the measured cavitation noise spectrum, and the one with higher elastic modulus has a higher noise frequency. According to the numerical validation, this phenomenon is attributed to the elastic response of different metals under the impaction of the collapsing bubbles, and the elastic modulus of the metals is the dominant mechanical factor that affects the frequency.